2018
DOI: 10.1140/epjc/s10052-018-5817-x
|View full text |Cite
|
Sign up to set email alerts
|

New feature of low $$p_{T}$$ p T charm quark hadronization in pp collisions at $$\sqrt{s}=7$$

Abstract: Treating the light-flavor constituent quarks and antiquarks whose momentum information is extracted from the data of soft light-flavor hadrons in pp collisions at √ s = 7 TeV as the underlying source of chromatically neutralizing the charm quarks of low transverse momenta ( p T ), we show that the experimental data of p T spectra of single-charm hadronsTeV can be well understood by the equal-velocity combination of perturbatively created charm quarks and those light-flavor constituent quarks and antiquarks. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…This property is the direct consequence of the equal-velocity combination (EVC) of constituent quarks and antiquarks at hadronization. We further demonstrated that EVC can self-consistently explain the data of p T spectra for different identified hadrons in high multiplicity pp and p-Pb collisions at LHC energies [20,[22][23][24] and in heavy-ion collisions in a wide collision energy range [25]. Taking advantage of rich data for hadronic v 2 in heavy-ion collisions, in particular, at RHIC BES energies [6][7][8]26,27], it is interesting to further study whether this EVC mechanism works for v 2 of hadrons or not.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…This property is the direct consequence of the equal-velocity combination (EVC) of constituent quarks and antiquarks at hadronization. We further demonstrated that EVC can self-consistently explain the data of p T spectra for different identified hadrons in high multiplicity pp and p-Pb collisions at LHC energies [20,[22][23][24] and in heavy-ion collisions in a wide collision energy range [25]. Taking advantage of rich data for hadronic v 2 in heavy-ion collisions, in particular, at RHIC BES energies [6][7][8]26,27], it is interesting to further study whether this EVC mechanism works for v 2 of hadrons or not.…”
Section: Introductionmentioning
confidence: 62%
“…We note that this extraction is only valid in the low p T range where the combination dominates D meson production. In previous studies [23,24], we found that experimental data for p T spectra of single-charmed hadrons in the range p T 8 GeV/c in pp and pPb collisions at LHC energies are well described by the EVC model. Therefore, experimental data of v 2 for D mesons with p T 8 GeV/c can be used to extract v 2 of charm quarks with p T 6 GeV/c in EVC model.…”
Section: Charm Quark V 2 From D Mesonsmentioning
confidence: 73%
See 1 more Smart Citation
“…Several mechanisms have been proposed to explain this enhancement. These mechanisms include colour reconnection beyond leading colour approximation [3], coalescence [4], and feed-down from several higher mass charm states as suggested by He and Rapp [5]. In this contribution, we report on measurements made of the charmed baryons…”
Section: Introductionmentioning
confidence: 99%
“…The model calculation from PYTHIA8 Monash [8] largely underestimates the measurement, the statistical hadronisation model (SHM) with excited charm baryon states predicted by the relativistic quark model (RQM) [9] can describe the measurement within uncertainties. The model calculations of Catania [10] and quark (re-)combination mechanism (QCM) [11] both including the coalescence process, also can describe the measurement. In general, PYTHIA8 implemented colour reconnection beyond the leading-colour approximation (CR-BLC) [12] better describes the Λ + c /D 0 ratio and Σ 0,++ c /D 0 ratio, which do not contain the strange quarks.…”
Section: Introductionmentioning
confidence: 99%